Observer-Based Tracking Control for Polysolenoid Linear Motor with Unknown Disturbance Load - Hong Quang Nguyen (Actuators, 2020)
Linear motors have been playing a crucial role in mechanical motion systems due to its ability to provide a straight motion directly without mediate mechanical actuators. This paper investigates tracking control problems of Polysolenoid Linear Motor, which is a particular type of permanent magnet linear motor in a tubular structure. In order to deal with unmeasurable velocity, our method proposes a novel observer guaranteed asymptotic convergence of the observer errors. Then, based on observed velocity, our method proposes controllers for position-velocity and current tracking control concerning an unknown disturbance load problem by using Lyapunov direct method. The proposed controllers ensure that the position-velocity tracking error converges to arbitrarily small values by adjusting control parameters. Finally, the validity and effectiveness of our approach are shown in illustrative examples.